ANALISIS INOVASI LAYANAN PENATAAN SISTEM MANAJEMEN SDM PADA KANTOR IMIGRASI KELAS I TPI KENDARI - Haswindah Limpo; Ibnu Hajar; Ummy Kalsum (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to identify and analyze the service innovation of HR management system management at the Immigration Office Class 1 TPI Kendari. The informants in this study were five people. The data collection techniques using observation, interviews and documentation. While the analytical tool used is qualitative data analysis techniques using triangulation techniques. Based on the results of the study it can be concluded that passport service innovation in terms of ikeni lapak (passport service between cities/districts), ikeni sapa (Kendari immigration ready to deliver your passport), ikeni salto (Kendari immigration to direct photos), ikeni blessing (Kendari immigration praying and alms), lako ikeni (Kendari immigration collective service) and ikeni yanti (Kendari immigration serving with heart) can provide good service to all users of immigration services.